Legal residency status and its relationship with health indicators among Syrian refugees in Lebanon: a nested cross-sectional study - Hala Ghattas; Jocelyn Dejong; Stephen J McCall; Sawsan Abdulrahim; Marie-Elizabeth Ragi; Berthe Abi Zeid; Hazar Shamas; Noura Joseph El Salibi; The CAEP study group (BMJ Global Health)
Background Failure to possess or renew legal residency permits increases the burden on a vulnerable refugee population. It risks detention or deportation, and hinders access to basic services including healthcare. This study aimed to examine the association between legal residency status and health of Syrian refugees living in Lebanon.Methods Data were from two independent nested cross-sectional studies collected in 2022 through telephone surveys. In the first study, all Syrian refugees aged 50 years or older from households that received humanitarian assistance were invited to participate. The second included all adult Syrian refugees residing in a suburb of Beirut. The exposure was self-reported possession of a legal residency permit in Lebanon. The self-reported health outcomes were mental health status, COVID-19 vaccine uptake, and access to needed healthcare services. Separate logistic regression models examined the association between lacking a legal residency permit and each health outcome, adjusted for age, length of stay in Lebanon, education, employment, wealth index and receipt of assistance.Results The first sample included 3357 participants (median age 58 years (IQR: 54–64), 47% female), of whom 85% reported lacking a legal residency permit. The second sample included 730 participants (median age 34 years (IQR: 26–42), 49% female), of whom 79% lacked a legal residency permit. In both studies, lacking a legal residency permit increased the odds of having poor mental health (adjusted odds ratio (aOR): 1.46 (95% CI: 1.07 to 1.99); aOR: 1.62 (95% CI: 1.01 to 2.60)) and decreased the odds of COVID-19 vaccine uptake (aOR: 0.66 (95% CI: 0.54 to 0.80); aOR: 0.51 (95% CI: 0.32 to 0.81)). In the subsample who needed primary healthcare, lacking a legal residency permit decreased the odds of access to primary healthcare, which was statistically significant in the second study (aOR: 0.37 (95% CI: 0.17 to 0.84)).Conclusions The majority of Syrian refugees from these two samples reported lacking a legal residency permit in Lebanon. This was associated with poor mental health and lower uptake of COVID-19 vaccination, potentially originating from fear of detention or deportation. These findings call for urgent action to support access to legal documentation for refugees in Lebanon.